2003
DOI: 10.1136/bmj.326.7399.1124
|View full text |Cite
|
Sign up to set email alerts
|

Iron supplementation for unexplained fatigue in non-anaemic women: double blind randomised placebo controlled trial

Abstract: Objective To determine the subjective response to iron therapy in non-anaemic women with unexplained fatigue. Design Double blind randomised placebo controlled trial. Setting Academic primary care centre and eight general practices in western Switzerland. Participants 144 women aged 18 to 55, assigned to either oral ferrous sulphate (80 mg/day of elemental iron daily; n=75) or placebo (n=69) for four weeks. Main outcome measures Level of fatigue, measured by a 10 point visual analogue scale. Results 136 (94%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
179
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(221 citation statements)
references
References 21 publications
8
179
0
9
Order By: Relevance
“…Using clinical recommendations, the study was to detect a minimum treatment effect of one point between treatment group and placebo. 12 Using effect size from a previous study, 3 we therefore powered our study to significantly detect a decrease by 1.8 points in the treatment group versus 0.8 in the placebo group (SD 2.0). With a power set at 0.9 and a significance level set at 0.05, 85 patients were required in each group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using clinical recommendations, the study was to detect a minimum treatment effect of one point between treatment group and placebo. 12 Using effect size from a previous study, 3 we therefore powered our study to significantly detect a decrease by 1.8 points in the treatment group versus 0.8 in the placebo group (SD 2.0). With a power set at 0.9 and a significance level set at 0.05, 85 patients were required in each group.…”
Section: Discussionmentioning
confidence: 99%
“…2 Verdon and coauthors found an improvement in fatigue following iron supplementation in nonanemic women with unexplained fatigue. 3 However, the hemoglobin levels of these patients were not available, which may have contributed to the ongoing debate about the appropriateness of reference limits defining anemia in women. 4,5 Thus, the effectiveness of iron supplementation in nonanemic menstruating women with major fatigue without an obvious clinical cause is unknown.…”
mentioning
confidence: 99%
“…While the authors made the case that iron deficiency anemia was clearly detrimental, it was not established whether iron deficiency in the absence of anemia was detrimental. More recent findings from controlled studies in healthy women have suggested a link between iron deficiency and fatigue (43)(44)(45)(46) or learning and memory (47).…”
Section: Discussionmentioning
confidence: 99%
“…As our results show, mean age at marriage of the women was 19.8 years (SD + 2.76). The average age at first childbirth was 20.88 years, as majority of them conceive within one year of marriage. This is in contrast to NFHS-3 finding, according to which more than half of women are married before the legal minimum age of 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…19 Verdon et al also documented that there was significant improvement in fatigue following iron supplementation in non-anaemic women with unexplained fatigue. 20 Hence, iron supplementation may be considered in family OPDs/MI Rooms of Military hospitals for women with unexplained fatigue who have normal haemoglobin levels but have underlying low ferritin levels.…”
Section: Discussionmentioning
confidence: 99%